Effective Insomnia Treatments: Investigation of Processes in Mindfulness and Cognitive Therapy. Issue 2 (8th June 2018) - Lee, Christopher William; Ree, Melissa J.; Wong, Mei Yin
Abstract : Understanding the underlying mechanisms of recovery from insomnia is an important goal for improving existing treatments. In a randomised controlled trial, 57 participants with insomnia disorder were given either cognitive therapy (CT) or mindfulness-based therapy (MBT) following 4 sessions of CBT. Each participant was assessed on process measures related to CT and MBT. MBT resulted in improvement on mindfulness process measures and the size of the improvement was significantly greater than achieved in the CT condition. Interestingly, CT and MBT both resulted in significant improvement on the cognitive process measures. Treatment outcome on the primary outcome measure (Insomnia Severity Index) was not predicted by type of treatment but was predicted by posttreatment scores on the cognitive process measures. The results suggest that changes in cognitive processes are especially important in treating insomnia, and that there are different therapeutic modalities through which this can be achieved.